The power of visual rethoric in transforming LGBT+ perceptions - Kulesh, Vitalii (My University, 2025)
This dissertation explores how visual rhetoric shapes public perception and challenges LGBTQ+ marginalisation by functioning as a tool of resistance, identity affirmation, and social transformation. In contexts where speech is censored or unsafe images become vital advocacy instruments. Drawing from semiotics, queer theory, rhetoric, and media studies, the research argues that visuals do not simply reflect social reality but actively construct it through symbolic power, emotional resonance, and ideological framing. Through historical and contemporary examples — from protest symbols to viral digital content — the study shows how visual activism generates solidarity, provokes empathy, and contests dominant narratives while exposing the instability and contested nature of visual meaning. Audience responses gathered through a qualitative survey demonstrate that interpretation, not representation alone, determines impact, shaped by platform logics and sociocultural context. LGBTQ+ viewers often experience activist imagery as validating and empowering, while non-LGBTQ+ reactions range from solidarity to resistance, highlighting the need for visual literacy and strategic framing. Ultimately, the dissertation positions visual culture as a central arena of political struggle, where inclusivity, accountability, and critical engagement are essential. Images do not merely accompany activism — they constitute it, offering a powerful language for justice, visibility, and cultural change in an increasingly algorithmic and polarised media landscape.

Esta dissertação explora de que forma a retórica visual molda a perceção pública e desafia a marginalização das pessoas LGBTQ+, funcionando como uma ferramenta de resistência, afirmação identitária e transformação social. Em contextos onde a liberdade de expressão é censurada ou insegura as imagens tornam-se instrumentos vitais de advocacia. Recorrendo à semiótica, à teoria queer, à retórica e aos estudos dos media, a investigação defende que os visuais não refletem simplesmente a realidade social, mas constroem-na ativamente através do poder simbólico, da ressonância emocional e da estruturação ideológica. Através de exemplos históricos e contemporâneos — desde símbolos de protesto até conteúdos digitais virais — o estudo demonstra como o ativismo visual gera solidariedade, provoca empatia e contesta narrativas dominantes, ao mesmo tempo que expõe a instabilidade e a natureza contestada do significado visual. As respostas do público, recolhidas através de um inquérito qualitativo, revelam que é a interpretação — e não apenas a representação — que determina o impacto, sendo esta moldada pelas lógicas das plataformas e pelo contexto sociocultural. Espectadores LGBTQ+ tendem a experienciar as imagens ativistas como validadoras e empoderadoras, enquanto as reações de pessoas não LGBTQ+ variam entre a solidariedade e a resistência, salientando a necessidade de literacia visual e de uma estruturação estratégica. Em última análise, a dissertação posiciona a cultura visual como um espaço central de luta política, onde a inclusão, a responsabilidade e o envolvimento crítico são essenciais. As imagens não acompanham simplesmente o ativismo — constituem-no, oferecendo uma linguagem poderosa para a justiça, a visibilidade e a mudança cultural num panorama mediático cada vez mais algorítmico e polarizado.
Keywords: Intersectionality; Narrative strategies; Queer visibility; Visual activism; Visual culture and identity